“They know AI, but they also know us”: student perceptions of EFL teacher identity in AI-enhanced classrooms in Jordan - Almashour, Mohamad; Aldamen, Hesham Abdel Karim; Jarrah, Marwan (Frontiers in Education, 2025)
IntroductionThe integration of artificial intelligence (AI) in education is reshaping classroom practices and teacher identity, particularly in English as a Foreign Language (EFL) contexts. This study investigates undergraduate perceptions of how AI impacts EFL teacher roles in Jordanian classrooms.MethodsUsing a qualitative design, semi-structured interviews were conducted with 20 third- and fourth-year EFL students at the University of Jordan. Thematic analysis was applied to identify patterns in student responses.ResultsFour major themes emerged: (1) the diminished centrality of teachers, (2) AI as a pedagogical double-edged sword, (3) the irreplaceable human element, and (4) reframing authority and expertise.DiscussionWhile students appreciate AI’s efficiency, they emphasize the enduring value of teacher empathy, cultural understanding, and relational engagement. The findings highlight the need for balanced AI integration that preserves human dimensions of teaching.ConclusionThe study underscores the evolving nature of teacher identity in AI-mediated contexts and provides implications for pedagogical training and policy in Jordan and similar contexts.